2019
DOI: 10.1101/662817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ginsenoside Rg1 defenses PC-12 cells against hydrogen peroxide-caused damage via up-regulation of miR-216a-5p

Abstract: BackgroundSpinal cord injury (SCI) is a destructive trauma accompanying with local injury, half of which cause chronic paralysis. Ginsenoside Rg1 exerts anti-apoptosis and anti-autophagy properties. Therefore, our goal was to study the protective mechanism of Rg1 in attenuating cell injury.MethodsMiR-216a-5p inhibitor was transfected into PC-12 cells, then cells were pre-treated by Rg1 and treated with 300 μM hydrogen peroxide (H2O2) for 24 h. CCK-8 and apoptosis experiments were done to test cell activity and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…More importantly, an investigation performed in primary cortical neuronal cells confirmed that elevating the expression of miR-216a could stimulate the neuroprotective effects on ischemic damages via targeting JAK2 both in vivo and in vitro [15]. Furthermore, a previous study specified that Ginsenoside Rg1, the primary active composition extracted from ginseng, exerted its protective roles against H 2 O 2 -triggered damages through elevating miR-216a-5p expression in PC12 cells [27]. Therefore, we suspected that CHR might exert its regulatory roles via mediating the expression of miR-216a as well.…”
Section: Discussionmentioning
confidence: 86%
“…More importantly, an investigation performed in primary cortical neuronal cells confirmed that elevating the expression of miR-216a could stimulate the neuroprotective effects on ischemic damages via targeting JAK2 both in vivo and in vitro [15]. Furthermore, a previous study specified that Ginsenoside Rg1, the primary active composition extracted from ginseng, exerted its protective roles against H 2 O 2 -triggered damages through elevating miR-216a-5p expression in PC12 cells [27]. Therefore, we suspected that CHR might exert its regulatory roles via mediating the expression of miR-216a as well.…”
Section: Discussionmentioning
confidence: 86%
“…To further clarify the mechanism, the PI3K inhibitor LY294002 was used to prove that the anti-apoptotic effect was achieved through the PI3K/Akt signaling pathway. Similarly, Rg1 exerts neuroprotection via the same pathway as Rb1 (Yi et al, 2019).…”
Section: Ginsenosides and Autophagymentioning
confidence: 99%